Molecular analysis of immune checkpoint inhibitor associated erythema nodosum-like toxicity - Xiaopeng Sun; Margaret L. Axelrod; Paula I. Gonzalez-Ericsson; Violeta Sanchez; Violeta Sanchez; Yu Wang; Jonathan L. Curry; Elizabeth J. Phillips; Yaomin Xu; Douglas B. Johnson; Justin M. Balko (Frontiers in Immunology)
PurposeImmune checkpoint inhibitors (ICIs) are increasingly used to treat advanced malignancy but can induce immune-related adverse events (irAE). The mechanisms behind these sporadic and sometimes life-threatening irAEs remain largely unexplored. Here, we present a case report and in-depth molecular analysis of an erythema nodosum (EN) like irAE occurring in a melanoma patient with isolated brain metastasis, aiming to explore the potential mechanism of this irAE.MethodsWe performed RNA and T cell receptor (TCR) sequencing on the patient’s resected brain metastasis and biopsy of EN-like irAE. Single cell RNA/TCR sequencing was conducted on the patient’s peripheral blood mononuclear cells (PBMC) at baseline, 3 weeks after ipilimumab and nivolumab combination therapy, during EN toxicity and after resolution.ResultsThe site of EN-like irAE showed a distinct accumulation of pro-inflammatory immune cells, accompanied by the upregulation of inflammatory and interferon response signatures. In addition, clonal expansion and activation of irAE-associated CD8 T cells and upregulation of monocyte-specific interferon signatures occurred concurrently with irAE onset.ConclusionThe unique immune landscape at the EN-like irAE could indicate that this irAE is distinct from anti-tumor immune and analogous non-ICI autoimmune milieus. Our data also suggests that systemic immune activation induced by ICI treatment, as reflected in PBMC, may help monitor the patient’s treatment response and access irAE risk.